1988
DOI: 10.1113/jphysiol.1988.sp016937
|View full text |Cite
|
Sign up to set email alerts
|

A chloride conductance activated by adenosine 3',5'‐cyclic monophosphate in the apical membrane of Necturus enterocytes.

Abstract: SUMMARY1. Intracellular potentials, C1-activity and membrane resistances were measured in Necturus small intestinal epithelium during C1-replacement experiments using conventional or Cl--selective double-barrelled microelectrodes. A Cl-conductance, located in the apical membrane and activated by cyclic nucleotides is demonstrated by ion-substitution experiments.2. The mean mucosal membrane potential (Em) was -35-5 mV. Removal of C1-from the mucosal medium by replacement with gluconate, evoked a sudden depolari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…However, the sequence indicated in Fig. 5 is quite similar to the anion selectivity sequence reported for C1-channels in Type II alveolar cells [25], in bovine cortical vesicles [17] and in Necturus enterocytes [8].…”
Section: Discussionsupporting
confidence: 51%
“…However, the sequence indicated in Fig. 5 is quite similar to the anion selectivity sequence reported for C1-channels in Type II alveolar cells [25], in bovine cortical vesicles [17] and in Necturus enterocytes [8].…”
Section: Discussionsupporting
confidence: 51%
“…A study on Necturus enterocytes has shown that a swelling-activated chloride conductance is present in the apical membrane of these cells (32). In addition, cell swelling may stimulate transepithelial chloride secretion in airway epithelium (33), the T 84 colonic epithelial cell line (34,35), HT-29Cl.19A intestinal epithelial cells (36), and rat ileum (25).…”
Section: Discussionmentioning
confidence: 99%
“…The intestine of this aquatic salamander, though a convenient model owing to the large size of its cells, lacks the complexity of the mammalian small intestine and is not organized into crypts and villi. In the salamander the current through the apical membrane is dominated by a Cl-conductance (Giraldez et al 1988) and that through the basolateral membrane is dominated by a K+ conductance (Valverde, Sheppard, Giraldez & Sepuilveda, 1991). Two types of K+ channel, a Ca2+-activated maxi-K+ channel and a smaller conductance channel (Sheppard et al 1988 a, b), are thought to underlie the two main types of K+ currents observed in isolated Necturus enterocytes in voltage-clamp experiments (Sheppard et al 1990;Valverde et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Small intestinal epithelial cells from Necturus are known to have an apical Cl-conductance which is activated by cellular cyclic AMP (Giraldez et al 1988) and by cell swelling (Giraldez, Valverde & Sepuilveda, 1989b). The corresponding single channel activity can behave as outwardly rectifying (Giraldez et al 1989a).…”
Section: Cl-currentsmentioning
confidence: 99%